Analysis of Physical Environment Factors and The Characteristics of Workers with Respiratory Complaints in an Aluminum Pot Industry - Yudha Eka Putra Suwanto (Universitas Airlangga, 2018)
Aluminum dust have sized less than 2.5 microns can cause disorders of the lung function. The International Labor Organization suggests that 21% of occupational-related deaths are respiratory diseases. The purpose of the research, namely analyzing the relationship of physical environment factors and the characteristics of workers with respiratory complaints. Physical factors of the environment that is in the form of levels of PM 2.5, temperature and humidity. Worker characteristics include age, gender, level of education, working period, the habit of smoking and the use of respiratory protective tool. The study was observational analytical research using cross sectional design. The characteristics of the environment in the form of levels of PM 2.5 measured using EPAM 5000, temperature and humidity are measured using termohygrometer. The characteristics of workers and respiratory complaints in identification using a questionnaire. Sample research is 52 respondents taken using random sampling system. The results of statistical tests using chi square obtained relationship between respiratory complaints with age (p=0,037). Respiratory complaints not related to levels of PM 2.5 (p=0,507), temperature (p=0,507), gender (p=0,343), level of education (p=1,000), work (p=1,000), the habit of smoking (p=0,281) and use of protective breathing (p=0,283). The conclude is respiratory complaints in this study on the influence by age. So the owner of the industry is expected to provide guidance about the dangers of dust exposure.